Prediction of the Strength of Energetic Materials Using the Condensed and Gas Phase Heats of Formation. Issue 4 (30th October 2014) - Kamalvand, Mohammad; Keshavarz, Mohammad Hossein; Jafari, Mohammad
Abstract The strength of energetic materials is one of the principal parameters to express their performance. Two new methods were introduced for the prediction of the strength of CaHbNcOd energetic materials through the Trauzl test. They are based on elemental composition and the condensed or gas phase heats of formation of energetic compounds. The model is based on the gas phase heat of formation, uses the group additivity method and requires only the molecular structure of the desired energetic compound. These methods provide more reliable predictions as compared to the best available theoretical methods. Some of the benefits of these new models are their accuracy, precision, simplicity, and low price.